(untitled) (Research, Society and Development, 2021)
The objective of the study was to report the clinical presentation and, the surgical correction of congenital phimosis in a young cat, by circumferential postioplasty. A cat, male, mixed breed, with four months of life, was admitted to the Veterinary Hospital of the State University of Londrina, complaining of dysuria, polyuria and polydipsia since birth, in addition to hematuria one day ago. On physical examination, wet dermatitis was observed in the scrotal region, with the presence of urine in the preputial cavity, and when trying to pull the patient’s penis for the evaluation, a preputial orifice with insufficient opening for exposure was identified. In view of the history, the patient’s age and physical examination, phimosis due to congenital stenosis of the preputial ostium was suggested as a diagnosis. The treatment instituted was correction surgery. A wedge-shaped incision was made in the craniodorsal face of the foreskin with an excision of about 3 mm, the mucosa of the ipsilateral edge of the foreskin was positioned in a simple discontinuous suture pattern, using a 5-0 non-absorbable suture. Ten days after the procedure, the animal was urinating in a jet, without further changes. Thus, performing the surgical correction of congenital phimosis in cats, using the circumferential postioplasty technique, is recommended, as there is resolution of the clinical changes. In addition, it was evident in the present study that the patient’s prognosis success was due to the knowledge of physiology and an efficient pediatric clinical examination.